Análisis de los ingresos tributarios recaudados por la intendencia regional de Loreto - SUNAT, periodo 2010 - 2015 - Ramos Araujo, José Alberto (2023)
Tax collection is essential to finance the execution of public works and current public spending. The objective of the investigation was to determine the behavior of the tax revenues collected by the Loreto Regional Administration - SUNAT, in the period 2010-2015; For this purpose, this research of the Quantitative type, Correlational level and Non-experimental design was carried out. The investigation concludes that the tax collection of the Loreto region had a variable behavior throughout the study period, with an increasing trend in the first three years and decreasing in the last three, starting from S /. 340,771,736.53 in 2010 until reaching the maximum value in 2012 that was S /. 429,221,390.22; to close 2015 with S /. 323,924,805.81. Tax revenue was S /. 2,226,564,287.46; corresponding to the "Internal Taxes" the sum of S /. 1,809,841,554.25 which represents 81.28% of the total, and the "Customs Taxes" the amount of S /. 416,722,733.21 equal to 18.72% of the total. In the "Internal Taxes" group, the one that contributed the most was the "Income Tax", having sought income of S/. 1,128,026,524.34, which represents 62.33% of the total. On the other hand, in the group of "Customs Taxes", the greatest contribution came from the "General Sales Tax" that raised the sum of S /. 291,865,806.41 which means 70.04% of the total, linked to the import of oil equipment.